EGFR and anti-EGFR nanobodies: review and update. (21st April 2021) - Sharifi, Jafar; Khirehgesh, Mohammad Reza; Safari, Fatemeh; Akbari, Bahman
Abstract: Targeted therapy is one of the favourable methods used in cancer treatment. Several recombinant proteins and small-molecules used for this aim include monoclonal antibodies, antibody fragments and peptides. Nanobody (Nb) is a camelid antibody fragment that is very effective in targeted therapy. Recently, several anti-EGFR (epidermal growth factor receptor) Nbs have been developed and utilised for diagnosis and therapy of EGFR overexpressing tumours. Anti-EGFR Nbs are used in drug delivery systems, photodynamic therapy (PDT) and/or conjugated to other molecules such as quantum dots (QDs), nanoparticles, liposome, tumour penetration peptides, neural stem cells (NSCs) and chimeric antigen receptor T cells (CAR T cells). In this review, we discussed the structure and function of EGFR and Nb, the current status of EGFR targeting, and recent developments in anti-EGFR Nbs. To gain sound insight into the issue at hand, we focused on the most powerful anti-EGFR Nbs.